Effects of Shallow Groundwater on Deep Groundwater Dynamics in a Slow-Moving Landslide Site - YOKOYAMA, Kenji; EGUSA, Tomohiro; IMAIZUMI, Fumitoshi; YAMASHITA, Hiroto; IKKA, Takashi (International Journal of Erosion Control Engineering, 2023)
A slow-moving landslide is a mass movement that has major societal impact because of its large sediment volume. The principal cause of landslides is increased pore water pressure in deep aquifer close to the slip surface. Elucidation of the behavior of deep groundwater is critical in the stability analysis of the slow-moving landslides. Shallow groundwater, which flows through the landslide regolith, can undergo vertical infiltration and thus make a major contribution to the formation of deep groundwater, but this has not been sufficiently elucidated. The aim of the present study was to investigate the effects of shallow groundwater on the dynamics of deep groundwater in a landslide regolith. At a landslide site, with an area of 4200 m2, the shallow and deep groundwater levels were observed. A 1-m-depth temperature survey and groundwater quality analysis were also performed. Water budget analysis using the groundwater level showed that in the former half of a major rainfall event, groundwater that infiltrates vertically in the landslide regolith plays a central role in raising the deep groundwater level. In addition, the preferential flow from shallow to deep aquifers is suggested to be important in that infiltration. The results of this study emphasize the importance of including the preferential flow from the shallow aquifer when modeling dynamics of deep groundwater.